2022
DOI: 10.1073/pnas.2121024119
|View full text |Cite
|
Sign up to set email alerts
|

Associations between forensic loci and expression levels of neighboring genes may compromise medical privacy

Abstract: A set of 20 short tandem repeats (STRs) is used by the US criminal justice system to identify suspects and to maintain a database of genetic profiles for individuals who have been previously convicted or arrested. Some of these STRs were identified in the 1990s, with a preference for markers in putative gene deserts to avoid forensic profiles revealing protected medical information. We revisit that assumption, investigating whether forensic genetic profiles reveal information about gene-expression variation or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Imputation has appeared in a variety of problems in forensic genetics; 21 , 22 , 23 , 31 , 32 , 33 , 34 its use for the Arizona search problem is one of an increasing number of scenarios in which loci external to forensic systems can assist in understanding forensic genetic matching. Imputation has enabled the matching of genetic records between profiles of SNP loci and profiles of STR loci, potentially linking SNP and STR databases in principle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imputation has appeared in a variety of problems in forensic genetics; 21 , 22 , 23 , 31 , 32 , 33 , 34 its use for the Arizona search problem is one of an increasing number of scenarios in which loci external to forensic systems can assist in understanding forensic genetic matching. Imputation has enabled the matching of genetic records between profiles of SNP loci and profiles of STR loci, potentially linking SNP and STR databases in principle.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 33 It can also help in testing STR loci for phenotypic associations while attempting to understand the phenotypes that might be associated with particular forensic profiles. 31 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…in LD with—surrounding single nucleotide polymorphism (SNP) markers, it is sometimes possible to identify CODIS and genome-wide SNP genotypes as coming from the same individual, even when the sets of markers in the two datasets are disjoint (Edge et al, 2017; Kim et al, 2018). Most recently, direct examination of the CODIS markers provides suggestive evidence that some of them are associated with gene expression levels in some tissues (Bañuelos et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…An acknowledgment that CODIS genotypes may be more revealing than previously assumed may prompt rethinking of the patchwork of highly variable local practices governing CODIS genotype collection, storage, and access (Joh, 2015; Murphy & Tong, 2020; Roth, 2019) and influence considerations regarding universal forensic DNA databases (Miller & Smith, 2022). We advocate, along with Kaye (2014), that biomedical literature continue to be monitored in order to ascertain the phenotypic information accessible to a person with access to CODIS profiles (Bañuelos et al, 2022; Wyner et al, 2020). More generally, we advocate that practices surrounding CODIS profiles should be informed by a framework that considers CODIS genotypes not as isolated pieces of information but as components of a genome connected via linkage disequilibrium produced by recombination, mutation, and our shared evolutionary history (Edge et al, 2017; Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, research has shown that these genetic markers have a regulatory role in gene expression. For instance, Bañuelos, M., et al demonstrated correlations between genotypes in the Combined DNA Index System (CODIS) loci and expression variations of the neighboring gene and, possibly, medical information [194]. Therefore, genetic privacy has become one of the major challenges for FDP because of the continuous improvements and advances in this technology [193].…”
Section: Ethical Issuesmentioning
confidence: 99%